Cellular Stress and General Pathological Processes - Gusev, Eugeny Yu.; Zotova, Natalia V. (Current Pharmaceutical Design, 2019)
From the viewpoint of the general pathology, most of the human diseases are associated with a limited number of pathogenic processes such as inflammation, tumor growth, thrombosis, necrosis, fibrosis, atrophy, pathological hypertrophy, dysplasia and metaplasia. The phenomenon of chronic low-grade inflammation could be attributed to non-classical forms of inflammation, which include many neurodegenerative processes, pathological variants of insulin resistance, atherosclerosis, and other manifestations of the endothelial dysfunction. Individual and universal manifestations of cellular stress could be considered as a basic element of all these pathologies, which has both physiological and pathophysiological significance. The review examines the causes, main phenomena, developmental directions and outcomes of cellular stress using a phylogenetically conservative set of genes and their activation pathways, as well as tissue stress and its role in inflammatory and para-inflammatory processes. The main ways towards the realization of cellular stress and its functional blocks were outlined. The main stages of tissue stress and the classification of its typical manifestations, as well as its participation in the development of the classical and non-classical variants of the inflammatory process, were also described. The mechanisms of cellular and tissue stress are structured into the complex systems, which include networks that enable the exchange of information with multidirectional signaling pathways which together make these systems internally contradictory, and the result of their effects is often unpredictable. However, the possible solutions require new theoretical and methodological approaches, one of which includes the transition to integral criteria, which plausibly reflect the holistic image of these processes.
Keywords: autophagy